RESEARCH OF ADVERTISING AND PR CAMPAIGN DEVELOPMENT OF THE COMPANY BRAND IN THE DIGITAL ENVIRONMENT - TANASIICHUK, Alona; HROMOVA, Olha; SHEVCUK, Anna (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The study is aimed at studying the impact of digital technologies and online communications on marketing and branding strategies. The effectiveness of using digital platforms, social networks, and other online tools for brand positioning in the digital space is analyzed. Special attention is paid to interaction with the audience, ways of influencing consumers, as well as monitoring and analyzing the results of digital campaigns. The results of the research will contribute to the improvement of advertising and PR strategies for the successful positioning of the company's brand in the online environment. The study is aimed at analyzing the impact of the digital environment on brand communication, developing effective communication and marketing strategies in the digital space. The paper examines in detail the role of advertising and PR campaigns, strategies in today's environment, including search marketing, social media marketing, banner advertising, crowd marketing and the impact of big data & AI on brand communication. It also explores the use of influencer marketing, hyper personalization and optimization of the advertising budget to achieve optimal results in the digital world. Studying these aspects can help companies improve the effectiveness of their communication strategies and attract target audiences in the virtual space. On the example of a company in the service sector, a general plan for a brand’s advertising and PR company was developed, geotargeting was proposed as an advertising and public relations strategy for the company, the budget allocation of the advertising and PR company plan was carried out by months and channels, which is an important aspect of effective financial management and will allow control and optimize expenses, distributing them rationally and taking into account the needs of each month, identify the most effective ways of promoting services, will contribute to the growth of sales and business profitability.
Keywords: brand communication; digital environment; communication strategy; advertising and PR campaign; advertising and PR strategies; search marketing; social media marketing; banner advertising; crowd marketing; big data & AI; influencer marketing; hyper personalization; advertising budget